Potencialidad del modelo de desarrollo del pueblo montubio y posibilidades de ser asumido por comunidades de la provincia de Loja - Troya Muñoz, Juan Carlos (2014)
In 2008, 40 communities of the cantons of the County of Loja ago: He/she will rot, Zapotillo, Puyango, Pindal, Celica, Chaguarpamba and Loja, present their respective documentation to be part of the Council of development of the Town Montubio of the Costa and subtropical areas "CODEPMOC ", the reason of adhering to is to look for solutions to their short term problems, to know the realities of the montubios of the coast, its organization form, their productive system, their projects of associative commercialization and the form of how they have ended up consenting to international markets. For the execution of the objectives, he/she was carried out a recovery from the existent historical information to level of the Executive Secretary of the Council of Development of the Town Montubio (CODEPMOC), considering some factors that allowed to know the historical process - cultural of conformation of the Town Montubio all this with the support of the provincial coordinations of the different counties that you/they are part of the Town Montubio. To determine the applicability of the pattern of endogenous development he/she was carried out shops with the organizations of the cantons of Saraguro, Celica, Puyango and Loja being able to carry out comparisons between the current reality of the producer and the advantages of this model's application. For finally to elaborate limits propositivos that potencien the pattern and their linking with the community. The conclusions of the present investigation work are the following ones: The Town Montubio is born of a very significant cultural historical process in our country, agglutinating to a great social community that is born of those producing of the costs of the coast and subtropical areas, being located in urban and rural areas of our country. The process of social development of the Town Montubio is born of the deep knowledge of its cultural reality, its vivencias and experiences, it prioritizes the man, the nature, the family, the community like the most important element in this process that it takes advantage of its ancestral wisdom, its cosmovisión and the nature to be developed in harmony with her. Product of this process the Town Montubio comes applying a model of endogenous and collective, human development that develops its natural activity of producing of basic foods with the concept of alimentary security, enlarged agriculture and I develop of the integrated system, obtaining as results a production of quality at low costs, with added value subjected to agrotransformación processes and associative commercialization.